2018
DOI: 10.18805/ijar.b-768
|View full text |Cite
|
Sign up to set email alerts
|

The effect of apple cider vinegar and mushroom stalk supplementation on laying hens

Abstract: The aim of this trial was to study the effects of consuming water with apple cider vinegar (ACV) and feed including mushroom (Agaricus bisporus) stalk (MS) on performance and certain egg characteristics. The hens were separated into four treatment groups (with 4 replicates and 6 hens per replicate). The experimental groups were control (not consumed ACV and MS), ACV (3 ml/l drinking water), MS (20 g/kg feed) and ACV+MS (combination). At the end of the experiment, among the performance criteria tested, body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…It is thought that acetic acid in the HFV content used in our study may cause a d ec rease in F I d ep en din g on th e c on centratio n (Table 2). W hile it is compatible with the results of our current study (Karaalp et al, 2018;Goharrizi et al, 2020;Hanchai et al, 2021;Rattanawut et al, 2021), it differs (Omidi et al, 2020;Al-Shammari and Batkowska, 2021;Sittiya et al 2021). We foresee that the reason for this situation is due to the difference in the material and method used in the research.…”
Section: Growth Performancesupporting
confidence: 86%
“…It is thought that acetic acid in the HFV content used in our study may cause a d ec rease in F I d ep en din g on th e c on centratio n (Table 2). W hile it is compatible with the results of our current study (Karaalp et al, 2018;Goharrizi et al, 2020;Hanchai et al, 2021;Rattanawut et al, 2021), it differs (Omidi et al, 2020;Al-Shammari and Batkowska, 2021;Sittiya et al 2021). We foresee that the reason for this situation is due to the difference in the material and method used in the research.…”
Section: Growth Performancesupporting
confidence: 86%
“…In addition, Wahyudi et al (2021) mentioned that administration of liquid probiotics had no significant effect on BWG, FI and FCR up to 4 weeks of age. Karaalp et al (2018) and Chabalala, (2022) stated that adding apple vinegar had no effect on growth performance of laying hens and broilers. In contrary, Allahdo et al (2018) found that supplementation of probiotic and apple vinegar had no significant differences during grower and finisher phases, but beneficial effects were noticed at 1-10 d of age of broilers.…”
Section: Broiler Performancementioning
confidence: 99%
“…Apple cider vinegar (ACV), which is the most commonly manufactured vinegar globally, contains various organic acid(s) and phenolic substances (Karaalp et al, 2018). The slow Orleans process is employed for the manufacture of high quality vinegars, the submerged process, which is now the main approach, does not employ surface providing materials and depends on carefully selected cultures of Acetobacter growing in aerated deep culture.…”
Section: Introductionmentioning
confidence: 99%